2014
DOI: 10.1182/blood.v124.21.723.723
|View full text |Cite
|
Sign up to set email alerts
|

Apobec Family Mutational Signatures Are Associated with Poor Prognosis Translocations in Multiple Myeloma

Abstract: Aberrant chromosomal translocations are seen in ~40% of presenting patients and predominantly involve the IGH locus at 14q32. The five main translocations involving the IGH locus are t(4;14), t(6;14), t(11;14), t(14;16) and t(14;20), which result in over-expression of MMSET/FGFR3, CCND3, CCND1, MAF and MAFB, respectively. In previous clinical trials we have shown that the t(4;14), t(14;16) and t(14;20) are associated with a poor prognosis. In initial sequencing studies of myeloma it has been noted that the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 0 publications
7
66
3
Order By: Relevance
“…Two of these were characterized by high mutation burden and >20% contribution from APOBEC (SBS2 +SBS13). Both patients had IGH translocations involving MAFB and MAFA, confirming the known association between these IGH translocations and high APOBEC mutational activity (Supplementary Data 1) 26,27 . Interestingly, these two cases were the only ones without detectable non-canonical activationinduced deaminase (AID) (SBS9) activity.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Two of these were characterized by high mutation burden and >20% contribution from APOBEC (SBS2 +SBS13). Both patients had IGH translocations involving MAFB and MAFA, confirming the known association between these IGH translocations and high APOBEC mutational activity (Supplementary Data 1) 26,27 . Interestingly, these two cases were the only ones without detectable non-canonical activationinduced deaminase (AID) (SBS9) activity.…”
Section: Resultssupporting
confidence: 69%
“…1c, d) 6,7,9,17,[24][25][26] . APOBEC (SBS2 and SBS13) was also confirmed as an essential mutational process, absent in only 9 patients (17%) 17,25,27,28 . While SBS2 was always the most common APOBEC signature (43/52; 83%), SBS13 activity was observed in 6 cases (11.5%) (Supplementary Data 2).…”
Section: Resultsmentioning
confidence: 90%
“…AID is implicated in oncogenic mutations and chromosomal translocations, especially those involving immunoglobulin genes, which results in B‐cell and plasma cell tumorigenesis . It has been reported that the AID/APOBEC‐mediated mutational signature is associated with poor prognosis of myeloma patients . Taken together, BCL6‐dependent AID upregulation is a threat to the genomic integrity of myeloma cells and thus may affect disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Dozens of myeloma driver genes have been identified. The most common occur in the RAS and NF-kB families, 12,14,16 with many mutations associated with the primary myeloma molecular subgroups suggesting the underlying background initiating event drives the acquisition of subsequent molecular abberations. 13 A number of these new technologies are now Clinical Laboratory Improvement Amendments certified and available for diagnostic use, while additional techniques such as DNA methylation analysis remain confined to research laboratories.…”
Section: Advances In Molecular Profiling Technologies Enabling the Idmentioning
confidence: 99%
“…These subgroups are also associated with a mutational signature (a characteristic combination of mutation types) associated with the activity of the mRNA editing enzyme APOBEC and have an increased number of mutations. 16 MAF and MAFb protein have been demonstrated to mediate resistance to proteasome inhibitors, 22,23 perhaps contributing to this subgroup's adverse outcome seen in most, 2,24,25 though not all, 26 studies. Images from left to right show G-band karyotyping, FISH, GEP data, SNP array data, and NGS data.…”
Section: T(4;14)mentioning
confidence: 99%